Investigation of the Filtration Properties of Medical Masks - (:unkn) unknown (Elsevier Ltd, 2010)
Medical masks are mostly produced from textiles. Weaving, knitting and nonwoven technologies are used to produce masks. But, nowadays, nonwoven technology is preferred for the mask production method. Nonwoven surfaces has good filtration properties. Mostly polyester and polypropylene fibers are used for mask production. Medical masks are designed to enable different functions. Generally masks have to protect from virus, bacterias, biological substances and particules in the air. Medical masks enable all these properties and produced according to application field. This is the first and initial results of the medical filtration project carried out by the authors. In this study particule filtration properties of different masks have been investigated. For each mask smallest particule size filtrated from the air accepted as the base for the comparison. © 2010 Woodhead Publishing Limited. All rights reserved.
Keywords: Filtration; Mask; Medical; Reaspiration